Necesidad de formación de talentos humanos en Educación Inicial para optimizar la calidad educativa y propuesta de una maestría para la Universidad Técnica de Cotopaxi. - Parreño Olmos, Ana Belén (2015)
Research on "Need Human Talents Training in Early Childhood Education to optimize the quality of education and proposing a Masters in Technical University of Cotopaxi" is important in the educational context for the fulfillment of the objectives of education at national, zonal and in the city of Latacunga, for this research sets out the objectives to meet the need for training of human talent in Early Childhood Education to optimize the quality of education in Zone 3 of territorial planning and proposes an Academic Program Masters with honors in Early Childhood Education to optimize the quality of education, the first has become a problem to recruit professional human talent suitable for that level and the second to prepare teachers for optimal management at this level of education. The methodology used in the investigation corresponds to the qualitative and quantitative approach, documentary and field mode; in the descriptive, exploratory and level relationship between variables; among the most relevant results in the investigative process, the following are mentioned: The teachers fully consider the special, specific, teacher training and upgrade training is an indicator of quality of education and considers the need for special teacher training through Professional Program Master of Science in Education with a major in Early Childhood Education. With the above background and with the support and sponsorship of an Institution of Higher Education, as the Technical University of Cotopaxi is designed and produced Program Professional Master of Science in Education, mention Initial, it follows the guidelines of the Scheme academic existing and new profile for submission of postgraduate programs delivered in August 2014, it will benefit directly to the student population mind children from 3-5 years of initial level area of influence, to achieve the much desired quality education